Computational Intelligence Methods for Bioinformatics and Biostatistics 8th International Meeting, CIBB 2011, Gargnano del Garda, Italy, June 30 - July 2, 2011, Revised Selected Papers - Biganzoli, Elia; Vellido, Alfredo; Ambrogi, Federico; Tagliaferri, Roberto (Lecture Notes in Bioinformatics,, 2012)
This book constitutes the thoroughly refereed post-proceedings of the 8th International Meeting on Computational Intelligence Methods for Bioinformatics and Biostatistics, CIBB 2011, held in Gargnano del Garda, Italy, in June/July 2011. The 19 papers, presented together with 2 keynote speeches, were carefully reviewed and selected from 24 submissions. The papers are organized in topical sections on statistical learning, genomics, computational intelligence for health at the edge, proteomics, intelligent clinical decision support systems (i-CDSS), bioinformatics, and data clustering.